Da formação inicial a constituição da docência: o ser professor de matemática e física - Marinho, Lucas Martins (Brasil, 2025)
From Initial Training to the Constitution of Teaching: being a Mathematics and Physics Science teacher is the object of investigation in this research, which aimed to understand how students in the Bachelor's Degree in Science: Mathematics and Physics at ICET/UFAM constitute their teaching identity in the unity of theory and practice, and specifically: to analyze the main academic, personal, and contextual factors that influence the process of building the teaching identity during the initial training of future Mathematics and Physics Science teachers; to identify the theoretical and practical contributions experienced in the disciplines and their relationship with the development of pedagogical praxis; to verify how the pedagogical practices experienced in the course, including teaching methodologies and assessments, impact the constitution of teaching identity; and to describe the challenges faced throughout the formative process that constitutes the identity of Mathematics and Physics Science teachers. It is a study with a qualitative approach, anchored in the theoretical contributions of Pimenta (1999), Fernandes (2024), Franco (2016), Prado (2013), Perrenoud (2000), Tardif (2012), among others, and quantitative for presenting dualization, estimation, and evaluation in the presentation of results. The data production devices were: systematic review based on Cronin, Ryan, and Coughlan (2008) and the application of a semi-structured questionnaire mediated by the studies of Santos (2020) and Cher, Diniz, and Ribeiro (2011). For data analysis, we used Sousa's (2014) content analysis technique, configured as comprehensive-interpretative of the narratives of Science: Mathematics and Physics undergraduates. The studies revealed that the constitution of the teaching identity of the undergraduates in Science: Mathematics and Physics occurs in the relationship between personal and formative experiences throughout the course, favoring the construction of multiple knowledge necessary for the development of teaching practice, that is, of being a teacher.